INHIBITION OF GLYCOGEN SYNTHASE KINASE 3 BETA IN ARTERIAL REPAIR AND STENT RE-ENDOTHELIALIZATION (2008)
A device having a kinase inhibitor for treating or preventing vascular disease in a subject and a method of treating a subject therewith, is disclosed. The device can be a stent coated with the kinase inhibitor. The kinase inhibitor can be a glycogen synthase kinase (GSK) inhibitor, such as a GSK-3β inhibitor. Coronary artery disease and ischemic heart disease can be treated.